2016
DOI: 10.1186/s12913-016-1819-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-perception of leadership styles and behaviour in primary health care

Abstract: BackgroundThe concept of leadership has been studied in various disciplines and from different theoretical approaches. It is a dynamic concept that evolves over time. There are few studies in our field on managers’ self-perception of their leadership style. There are no pure styles, but one or another style is generally favoured to a greater or lesser degree. In the primary health care (PHC) setting, managers’ leadership style is defined as a set of attitudes, behaviours, beliefs and values. The objectives of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(21 citation statements)
references
References 26 publications
1
10
0
2
Order By: Relevance
“…TL is characterized by individual consideration, intellectual stimulation, inspirational motivation and idealized influence (Doody & Doody, 2012). Transactional leadership is another common leadership style (Solà, Badia, Hito, Osaba, & Del Val García, 2016); it is characterized by management by exception and contingent rewards. Other leadership styles include Laissez-faire leadership, authentic leadership, resonant leadership (Laschinger, Wong, Cummings, & Grau, 2014), relational, situational or task-oriented leadership, and situational leadership (McCay, Lyles, & Larkey, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…TL is characterized by individual consideration, intellectual stimulation, inspirational motivation and idealized influence (Doody & Doody, 2012). Transactional leadership is another common leadership style (Solà, Badia, Hito, Osaba, & Del Val García, 2016); it is characterized by management by exception and contingent rewards. Other leadership styles include Laissez-faire leadership, authentic leadership, resonant leadership (Laschinger, Wong, Cummings, & Grau, 2014), relational, situational or task-oriented leadership, and situational leadership (McCay, Lyles, & Larkey, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Alloubani et al (2014) in a review of effects of leadership styles on quality of services in health care found that transformational leadership characteristics have positive effects on organizational outcomes, including: ‘teamwork success, effectiveness, staff satisfaction, commitment and extra effort and others’. Other studies have also shown that strengthening leadership can increase the chances of improving performance ( Lembani et al 2015 ; Sola et al 2016 ). Al-Sawai (2013) further emphasized the need for effective leadership to focus on the dynamic relationships between leadership values, culture, capabilities and the organizational context anchored by a high level of self, team and organizational awareness.…”
Section: Discussionmentioning
confidence: 99%
“…These aspects of leadership style, such as use of data to improve service delivery, supportive leadership, teamwork have been reported in other studies ( Puoane et al 2008 ; Curry et al 2012 ; Lembani et al 2015 ). Sola et al (2016) study on self-perception of leadership styles and behaviour in primary health care classified this leadership style as ‘transformational’ and explained that it encourages teamwork, collaboration, empathy and the acceptance and use of innovativeness which results in improvement of outcomes as compared to the more rigid and bureaucratic leadership styles. Similar observations were made by other studies on transformational leadership ( Schaubroeck et al 2007 ; Top et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nesse contexto, pesquisadores têm demonstrado relação entre modelos de liderança contemporâneos e melhores resultados referentes à segurança do paciente e à satisfação dos profissionais, fatores esses que podem contribuir para a melhoria da qualidade da assistência (6)(7) . Dentre esses modelos de liderança, têm sido apontadas na literatura a Liderança transacional (8) , Liderança transformacional (9) , Liderança autêntica (10) , e a Liderança coaching, sendo essa última pautada por um processo de promoção e estímulo da aprendizagem, com orientação prática em busca do alcance de metas relacionadas ao desenvolvimento técnico e pessoal (11)(12) .…”
Section: Introductionunclassified